ANALISIS VOLATILITAS HARGA KOMODITAS HORTIKULTURA STRATEGIS DI PROVINSI BENGKULU - Hariz Eko Wibowo; Ridha Rizki Novanda (Universitas Teuku Umar, 2023)
Economic growth was caused by unstable inflation which made it difficult for the public to carry out production, consumption and investment. Therefore, the purpose of this study is to analyze the level of volatility of strategic horticultural commodity prices in the Bengkulu Province which has an impact on inflation. The data used is monthly time series data for horticultural strategy commodity prices in Bengkulu Province from July 2017 to December 2022. The horticultural strategy commodities studied were shallots, red chilies and cayenne pepper. The data used is secondary data sourced from the National Strategic Food Price Information Center. Price volatility analysis uses a time series model with the help of R studio software. Forecast results using the ARIMA model for shallot prices, red chili prices, and cayenne pepper prices show relatively stable prices. The highest level of price volatility among horticultural commodity strategies in Bengkulu Province is red chili, followed by cayenne pepper, and then shallots. The volatility of the shallot price is 14.33%. Red chili price volatility is 20.83%. The price volatility of cayenne pepper is 18.66%. This shows that the volatility levels of shallot prices, red chili prices, and cayenne pepper prices are still under control and this is reinforced by the results that the model does not have an ARCH effect. Several anomalies such as prices that rose significantly in June 2022 were due to a decline in commodities due to farmers reducing the number of plants in line with high fertilizer prices, especially in Rejang Lebong Regency. This is also the impact of the post-pandemic.